2020
DOI: 10.1002/sono.12244
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic ultrasounds referred from the emergency department: Agreement between sonographer findings and radiologists' reports

Abstract: Introduction: When radiologists are not available, sonographers may be able to provide an interim report, especially for patients referred from emergency or in remote clinics. The aim of this study was to compare the agreement of diagnostic findings between sonographers and radiologists for patients referred from the emergency department for pelvic ultrasound. Methods: Sonographer findings and corresponding radiologists' reports of consecutive pelvic ultrasound examinations referred from the emergency departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…14 Another 2021 Australian study comparing agreement levels between radiologists and sonographer's pelvic ultrasound findings concluded that sonographers could provide accurate interim reports when radiologists reports are delayed. 17 Overseas studies support these findings. 15,[18][19][20] A European study reported that in the UK and Norway, radiographers provided full ultrasound definitive reports and also provided advice on further ultrasound investigations.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…14 Another 2021 Australian study comparing agreement levels between radiologists and sonographer's pelvic ultrasound findings concluded that sonographers could provide accurate interim reports when radiologists reports are delayed. 17 Overseas studies support these findings. 15,[18][19][20] A European study reported that in the UK and Norway, radiographers provided full ultrasound definitive reports and also provided advice on further ultrasound investigations.…”
Section: Introductionmentioning
confidence: 78%
“…Information collected for the study included agreement rates, recommendations for further examinations, types of ultrasound examinations and clinical indications. The researcher scored the level of agreement by comparing the sonographic findings to those of the radiologists' reports by utilising four previously published diagnostic agreement scoring criteria 14,17 as follows:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sonographers are highly accurate diagnosticians whose diagnostic performance in US has been shown to be on a par with that of radiologists in a number of studies. [23][24][25][26][27][28][29][30] There is therefore no reason to suspect that under the additional pressure of a pandemic, the sonographer's diagnostic performance would somehow become compromised.…”
Section: Discussionmentioning
confidence: 99%